MENGUKUR KONSUMSI BAHAN BAKAR PADA SEPEDA MOTOR MATIC MENGGUNAKAN CHASSIS DYNAMOMETER UNTUK MENDUKUNG PENERAPAN PERILAKU ECO-DRIVING - Kemas Muhammat Abdul Fatah; Syarifudin, Mohammad; Saputra, Anam (PPPM POLTESA, 2023)
Global warming is the cause of climate change which is a threat to environmental destruction in the future, and one way to prevent global warming is to reduce the consumption of fossil fuels in vehicles. Technological improvements and alternative fuel use can be the solution to reducing fossil fuel consumption, but these are a partial solution. It requires a change in driver behavior when operating a motorized vehicle, called eco-driving. One of the behaviors in eco-driving is a behavior related to vehicle maintenance. The aim of this study is to provide simple manual for owners of automatic motorcycle regarding air filters and continuously variable transmission (ctv) maintenance. This study used a chassis dynamometer to determine the effect of the dirtiness rate the air filter and the wear rate the roller weight than fuel consumption. The findings show that the dirtier the air filter and the more wear the roller weight, the more the fuel consumption. Regarding eco-drive, the finding can be socialized to the larger community because they can be simple manual for owners of automatic motorcycle so that efforts to decrease fossil fuel consumption can be achieved.